1983
DOI: 10.1192/bjp.142.2.111
|View full text |Cite
|
Sign up to set email alerts
|

The Prognosis of Depression in Old Age

Abstract: The paper describes a one year prospective study of 124 elderly depressed patients. Only one third of the group had a good outcome. Poor outcome was associated with severity of initial illness, those with depressive delusions having a particularly poor outcome. Outcome was also influenced by physical health problems and severe life events in the follow-up year. Social class differences in outcome were thought to be due to class differences in the experience of severe life events. There was no evidence that an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
188
7
4

Year Published

1984
1984
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 574 publications
(214 citation statements)
references
References 15 publications
15
188
7
4
Order By: Relevance
“…The long-term prognosis for depression in later life has generally been considered mixed with only one quarter to one third of the patients robustly well at 1-3 years of follow-up (Murphy, 1983;Post et al, 1992;Cole et al, 1999;Beekman et al, 2002; for a review see Mitchell and Subramaniam, 2005). Once recovered from depressive symptoms, older people have a high risk of recurrence, with rates ranging between 15 and 50% (Hinrichsen and Hernandez, 1993;Little et al, 1996;Flint and Rifat, 1997;Kivela et al, 2000;Beekman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The long-term prognosis for depression in later life has generally been considered mixed with only one quarter to one third of the patients robustly well at 1-3 years of follow-up (Murphy, 1983;Post et al, 1992;Cole et al, 1999;Beekman et al, 2002; for a review see Mitchell and Subramaniam, 2005). Once recovered from depressive symptoms, older people have a high risk of recurrence, with rates ranging between 15 and 50% (Hinrichsen and Hernandez, 1993;Little et al, 1996;Flint and Rifat, 1997;Kivela et al, 2000;Beekman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Major depression in older persons over longer follow-up periods exhibits a chronic remitting course in most clinical studies (86)(87)(88)(89)(90)(91). In a 6-year follow-up of elderly depressives, 31% recovered and remained well, 28% suffered at least one relapse but recovered, 23% only partially recovered, and 17% remained depressed throughout the follow-up (86).…”
Section: Course Of Late-life Depressionmentioning
confidence: 99%
“…It must be said that some authors, like Murphy 7 have not found consistent relationships between pseudo dementia and the appearance of true dementia on follow-up. The present author suggests some reasons for this interesting aspect:…”
Section: Comments and Conclusionmentioning
confidence: 99%